Measuring the global 21-cm signal with the MWA-I: improved measurements of the Galactic synchrotron background using lunar occultation. Issue 4 (6th September 2018) - McKinley, B; Bernardi, G; Trott, C M; Line, J L B; Wayth, R B; Offringa, A R; Pindor, B; Jordan, C H; Sokolowski, M; Tingay, S J; Lenc, E; Hurley-Walker, N; et al.
ABSTRACT: We present early results from a project to measure the sky-averaged (global), redshifted $21\, $ cm signal from the Epoch of Reionization (EoR), using the Murchison Widefield Array (MWA) telescope. Because interferometers are not sensitive to a spatially invariant global average, they cannot be used to detect this signal using standard techniques. However, lunar occultation of the radio sky imprints a spatial structure on the global signal, allowing us to measure the average brightness temperature of the patch of sky immediately surrounding the Moon. In this paper, we present one night of Moon observations with the MWA between 72–230 MHz and verify our techniques to extract the background sky temperature from measurements of the Moon's flux density. We improve upon previous work using the lunar occultation technique by using a more sophisticated model for reflected 'earthshine' and by employing image differencing to remove imaging artefacts. We leave the Moon's (constant) radio brightness temperature as a free parameter in our fit to the data and as a result, measure T moon  = 180 ± 12 K and a Galactic synchrotron spectral index of −2.64 ± 0.14, at the position of the Moon. Finally, we evaluate the prospects of the lunar occultation technique for a global EoR detection and map out a way forward for future work with the MWA.